HUBUNGAN ANTARA AIR LIMBAH RUMAH TANGGA DENGAN LINGKUNGAN HIDUP - Nurul Jannah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Domestic wastewater is all wastewater originated from households or office buildings activities such as kitchen sink, bathroom, and laundry exclude the discharge of toilet. The wastewater contain chemicals that must be treated to avoid environment pollution which affects the environmental health. Before the treatment, the characterization of wastewater should be determined in order to attain the proper action.